Self-Love and Self-Acceptance in the Student Body: A Feminist Pedagogical Study in Christian Education - Nole, Otniel Aurelius; Lauterboom, Mariska (Tumou Tou, 2025)
Christian education has a positive influence on students every time. Christian education also provides opportunities for students to express their life experiences while educating them about body appreciation. This research analysed the significance of self-love and self-acceptance of the student body in Christian education from feminist pedagogy. This research method was qualitative, using a literature review approach, and data was collected by interviewing grade X adolescents at one of the public high schools in Palu. This research showed that adolescents apply life with the value of self-love and self-acceptance for their bodies. They also experienced caring educators and Christian education learning that supported development and growth.